2013
DOI: 10.4236/ape.2013.31006
|View full text |Cite
|
Sign up to set email alerts
|

Masters Athletes: No Evidence of Increased Incidence of Injury in Football Code Athletes

Abstract: The World Masters Games, held quadrennially, is the largest international sporting competition in terms of participant numbers. Yet this cohort remains proportionately under investigated. An online survey using an open-source specialized survey application software program was utilized to investigate the 2009 Sydney World Masters Games (SWMG) football code athletes (association football, touch football, rugby union). A total of 931 masters at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
(24 reference statements)
2
7
0
Order By: Relevance
“…Climstein et al (2012) concluded that the incidence of injury was not sufficient to warrant a suggestion to not participate due to injury risk. This finding, similar to Walsh et al, (2013c), was considered a positive result due to the evidence health benefits from exercise.…”
Section: Injury Patternssupporting
confidence: 61%
See 3 more Smart Citations
“…Climstein et al (2012) concluded that the incidence of injury was not sufficient to warrant a suggestion to not participate due to injury risk. This finding, similar to Walsh et al, (2013c), was considered a positive result due to the evidence health benefits from exercise.…”
Section: Injury Patternssupporting
confidence: 61%
“…There were also no significant age related changes in injury nature (classification type, location, incidence, time off work or training) (Walsh et al, 2013c). Therefore the premise of masters football code athletes having a higher incidence of injury as compared to younger athletes was not supported (Walsh et al, 2013c).…”
Section: Injury Patternsmentioning
confidence: 98%
See 2 more Smart Citations
“…Due to the fact that masters athletes adhere to higher levels of systematic training than a sedentary ageing population, a reduced recovery capacity would not only have a negative effect on training quality and sports performance but could also increase the risk of musculoskeletal injury. At present, the research reports contradictory findings when investigating injury rates in masters athletes with studies reporting less incidence of injury (Heazlewood et al, 2014) and no difference in the incidence of injury (Walsh et al, 2013) in masters athletes when compared to younger cohorts in both team sports and swimming. However, an increase incidence of injury has been reported in masters runners compared to younger runners (McKean, Manson, & Stanish, 2006), specifically overuse injuries (Knobloch, Yoon, & Vogt, 2008).…”
Section: Recovery and Incidence Of Injurymentioning
confidence: 99%